Evaluation of Performance Service Quality at Private Universities - Muhammed Omer Ali; Cemil Top (Eurasian Journal of Management & Social Sciences)
In today’s marketplace, whether in manufacturing or the service business, it is vital to prioritize customer demands. Managers in the service industry are subject to external influences; they place a premium on customer satisfaction, which has resulted in the continuous growth of service organizations’ performance. While this is occurring, it is vital to comprehend and quantify customer expectations. Numerous efforts at quantifying service quality using the SERVQUAL paradigm have been attempted. The goal of this study is to analyze the ideas and elements impacting the quality of services using a modified SERVQUAL model, and then to assess the quality of services using the suggested Grey Analytic Hierarchy Process (G-AHP (Grey Analytic Hierarchy Process)) and Multilevel Grey Evaluation models (GST). To demonstrate our strategy, we will conduct a case study on the performance of service quality in Kurdistan Sulaymaniyah’s higher education institutions, as the data indicates that the most crucial factor for universities is the communication quality of staff with students, followed by service depth and intensity, and the least crucial factor for universities is external building beautification.